(untitled) (Philippine, 2010)
Strategy 2020 sets the long-term strategic framework of the Asian Development Bank (ADB) for 2008–2020. During this period, ADB lending and technical assistance operations in Asia and the Pacific will emphasize inclusive economic growth, environmentally sustainable growth, and regional integration. The Sustainable Transport Initiative Operational Plan provides details of how ADB will update its operations in the transport sector in line with Strategy 2020. ADB will focus on creating transport systems that are accessible, safe, affordable, and environment-friendly.
Keywords: Transportation,Public transportation,Giao thông vận tải,Giao thông công cộng; Economic aspects,Khía cạnh kinh tế